2018
DOI: 10.1111/ases.12471
|View full text |Cite
|
Sign up to set email alerts
|

Is fascial defect closure with intraperitoneal onlay mesh superior to standard intraperitoneal onlay mesh for laparoscopic repair of large incisional hernia?

Abstract: For large incisional hernia repair, IPOM-Plus seems to be more effective than sIPOM in terms of reducing mesh bulging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
(68 reference statements)
3
24
0
Order By: Relevance
“…We limited the maximum diameter of the defect to 6 cm to avoid excessive tension after the fascial closure. In recent studies, intracorporeal defect closure was preferably indicated for defects less than or equal to 10 cm, whereas extracorporeal closure, with relaxing incision or the endoscopic anterior component separation, was performed for larger defects (greater than 10 cm) . Accordingly, we may be able to extend the application of our technique to defects up to 10 cm.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We limited the maximum diameter of the defect to 6 cm to avoid excessive tension after the fascial closure. In recent studies, intracorporeal defect closure was preferably indicated for defects less than or equal to 10 cm, whereas extracorporeal closure, with relaxing incision or the endoscopic anterior component separation, was performed for larger defects (greater than 10 cm) . Accordingly, we may be able to extend the application of our technique to defects up to 10 cm.…”
Section: Discussionmentioning
confidence: 96%
“…Laparoscopic incisional hernia repair (LIHR) has generally been supported by the recent literature (1)(2)(3). Defect closure during LIHR has also been advocated to reduce seroma, mesh bulge, and hernia recurrence (2)(3)(4)(5)(6)(7)(8)(9). Using barbed suture (BS) is considered beneficial because of improved tissue approximation, even distribution of tissue length, and reduced strangulating force (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It took 1 month for discontinuing analgesic agents. Although a meta-analysis demonstrated that postoperative pain with defect closure appeared to be transient [6] , a recent study showed that 14% of patients with IPOM-plus had pain at 3 months whereas those with sIPOM did not experience such pain [12] . Defect closure inevitably oppose to the ‘tension-free concept’ in hernia surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fascial defect closure has been advocated for reduction of seroma [6] , [9] , mesh bulge [6] , [10] , and recurrence rates [9] , [10] , although conflicting reports have also been published [11] , [16] . A recent study showed that defect closure with intraperitoneal onlay mesh (IPOM-plus) was more effective than standard intraperitoneal onlay mesh (sIPOM) in terms of reducing mesh bulge, for large hernias (greater than 10 cm in diameter) [12] . In the present case, the defect size was 14 cm (longitudinal) × 10 cm (horizontal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation